Réponses

2013-03-16T19:24:47+01:00

 a.4x = 3/5          
x = 3/(5*4) = 3/20

b.2/3 x = 7    
ici tu multipli par l'inverse car tu passe ta fraction de l'autre cote :
x = (7*3)/2 = 21/2
 
c.6/5 x = -7/11
meme chose que le b
x = (-7*5) / (11*6) = -35/66 divisible par 6 donc x = -5/11
 
d.-7 x = 4/-3
x = 4/(-7*(-3)) = 4 / 21
           
e.-3/2 x =5
x= (5*2)/(-3) = -(10/3)
           
f.-5/7 x = -2/-3
x = (-2*7)/(-3*-5) = -14/15
     
g.5x/7=0
x = 0 ici c'est evident

h.-3/2x=-7/11
x = (-7*2)/(11*(-3)) = -14/(-33) = 14/33

Voila :)
Bon courage 

2013-03-16T19:28:31+01:00

a. 4x = 3/5

x = 3/4x5

x = 3/20

 

b. 2/3x = 7

x = 7x3/2

x = 21/2

 

c. 6/5x = -7/11

x = -7x5/11x6

x = -35/66

x = -5/11

 

d. -7x = 4/-3

= 4/3x7

= 4/21

 

e. -3/2x = 5

x = 5x2/-3

x = 10/-3

 

f. -5/7x = -2/-3

x = (-2)x7/(-3)x(-5)

x = -14/15

 

g. 5x/7 = 0 

x = 0

 

h. -3/2x = -7/11

x = (-7)x2/11x(-3)

x = 14/33

 

i. -4/3 = -5/-11x

(-4)x(-11)/(-5)x3 = x

x = 44/-15